ANALISIS PROFITABILITAS BANK UMUM GO PUBLIC PADA BURSA EFEK INDONESIA (BEI) - Akhmad Reza Liannoor (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2014)
The rapid development of the banking world today is to encourage banks to improve their performance in competition between banks for customers. One tool for assessing bank performance is Return on Assets ratio (ROA). The purpose of this study is to analyze the effect of CAR, NPL, LDR, BOPO to ROA on the banks go public in Indonesia Stock Exchange the period 2007-2011. Based on the results of hypothesis tests conducted it was found that the F test showed independent variable CAR ratio, NPL, LDR, ROA, simultaneous or simultaneously effect of the variable ROA, can be seen from the calculated value of the F test 191.77> F-table 2.467. To test T concluded that the variables NPL and bopo significant negative effect so it can dikatankan ROA hypothesis that negatively affect profitability (ROA) is acceptable, while the variable CAR is not negative and not positive LDR variable, so the hypothesis that the CAR positive effect on profitability (ROA) is unacceptable as well as variables which hypothesis holds LDR LDR positive effect on profitability (ROA) is not acceptable. While the test of determination R2, Independent variables influence the dependent variable is large enough, judging from the value of the coefficient R2 is equal to 68.9522% 31.0478% while the remaining approximately explained by other variables that are not included in this research model.